Characteristics of Poly ENT HN Patients at Umbu Rara Meha Hospital and Physical Examination Features Obtained in Cases of Chronic Suppurative Otitis Media (CSOM) Benign Type and Malignant Type - Grisnawati Hamaduna, Bopy; Sunantara Astrea, I Made; Alexander Dira Damanik, Michael (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Chronic suppurative otitis media (CSOM) is a chronic infection of the middle ear which has been in the process for more than 2 months, which is characterized by a perforation of the tympanic membrane and continuous or intermittent discharge from the ear canal. In developing countries like Indonesia, the incidence of CSOM is quite high. Objective: to find out the characteristics of patient visits to the ENT polyclinic at Umbu Rara Meha Hospital and to find differences in the results of physical examinations for the Benign/ Benign type CSOM and the Danger/Malignant type of CSOM.  Method: The type of research used is observational analytics with a cross sectional design. Results and Discussion: based on the characteristics of patients visiting the ENT HN polyclinic, it was found that the dominant patients visiting the ENT HN polyclinic were male patients 50.7%, the age group 21-30 years 23% and ages 0-10 years 18.4%, most residents in cities who visiting Kambajawa 16.2%, high school education level 34.6%, Christianity 62.5%, using BPJS payments 51.5% and coming from the Sumba tribe 54.4%. The top 3 diseases in the ENT HN field are obturan cerumen 18.36%, rhinosinusitis 13.97% and cases of CSOM 12.2%. Conclusion: CSOM is included in the top three lists of the ten most common diseases at Umbu Rara Meha Hospital, determining the type of CSOM including the Benign or benign type or the malignant or malignant type will determine the appropriate therapeutic action and the prognosis of the patient's disease.